Polarization-Induced Interface and Sr Segregation of in Situ Assembled La0.6Sr0.4Co0.2Fe0.8O3−δ Electrodes on Y2O3–ZrO2 Electrolyte of Solid Oxide Fuel Cells - Chen, K.; Li, N.; Ai, N.; Cheng, Yi; Rickard, W.; Jiang, S. (American Chemical Society, 2016)
© 2016 American Chemical Society.Application of cobaltite-based electrodes such as La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) on Y2O3-ZrO2 (YSZ) electrolyte in solid oxide fuel cells (SOFCs) generally requires the use of a doped ceria barrier layer to prevent the interaction between LSCF and YSZ during sintering at high temperatures. In this paper, we report for the first time an in situ assembly approach to directly incorporate LSCF cathode to YSZ electrolyte without the use of a doped ceria barrier layer and without presintering at high temperatures. A Ni-YSZ anode-supported YSZ electrolyte cell with an in situ assembled LSCF electrode exhibits a peak power density of 1.72 W cm-2 at 750 °C. However, the cell performance degrades significantly at 500 mAcm-2 and 750 °C. The results indicate that cathodic polarization not only induces the formation of the interface but also accelerates the Sr segregation. The segregated Sr migrates to the LSCF electrode/YSZ electrolyte surface and forms an SrO layer. Using a Sr-free LaCoO3-d composite cathode overcomes the Sr segregation problem, showing an excellent peak power density of 1.2 Wcm-2 and good stability at 750 °C for over 100 h. The present study shows that cobaltite-based perovskites can be directly used on YSZ-based electrolyte via the in situ assembly providing an effective means to advance the application of highly active mixed ionic/electronic conducting cathodes to YSZ electrolyte-based SOFCs.